Determination of Arsenic and Some Heavy Metals Levels in Roadside Soils and Leaves of Aleppo City, Syria - Aziz Ramadan, Abdul; Mandil, Hasna (Asian Journal of Chemistry, 2010)
The concentration of As, Pb, Cd, Cr, Ni, Cu, Mn, Fe and Zn in soils and leaves of trees (pine, cypress, quinquine, ligastrium and azedarach) on both sides of the roads in the Aleppo city i.e., Bab Al-Faraj, Saadallah Al-Jabiri Square, Nile Street and Western Ring Road have been carried out using atomic absorption spectroscopy. It was found that the amount of pollution vary according to the element, location, traffic, weather conditions, population, density of buildings and the type of trees. The levels of all elements were decreased according to the mentioned sequence sites. Pollutants in leaves were as follows (ppm): As: 3.7-58; Pb: 5.8-22.4; Cd: 0.20- 0.76; Cr: 1.6-3.2; Ni: 0.14-1.08; Cu: 4.5-15.8; Mn: 1.6-10.5; Fe: 20.3-62.1 and Zn: 7.5-28.1 and in the soil under the trees as follows (ppm): As: 78-618; Pb: 133-940; Cd: 5.7-30.4; Cr: 14.0- 73.2; Ni: 3.8-34; Cu: 87-658; Mn: 62-436; Fe: 510-3614 and Zn: 162-1195. This study shows that the densely populated areas and buildings with heavy traffic (within the city) are strongly contaminated with arsenic and heavy metals more than other regions, which adversely affects public health. The trees planting on both sides of the streets effectively reduce the air pollutants.